The development of emotion processing of body expressions from infancy to early childhood: A meta-analysis - Vuong, Quoc C.; Geangu, Elena (Frontiers in Cognition, 2023)
Body expressions provide important perceptual cues to recognize emotions in others. By adulthood, people are very good at using body expressions for emotion recognition. Thus an important research question is: How does emotion processing of body expressions develop, particularly during the critical first 2-years and into early childhood? To answer this question, we conducted a meta-analysis of developmental studies that use body stimuli to quantity infants’ and young children’s ability to discriminate and process emotions from body expressions at different ages. The evidence from our review converges on the finding that infants and children can process emotion expressions across a wide variety of body stimuli and experimental paradigms, and that emotion-processing abilities do not vary with age. We discuss limitations and gaps in the literature in relation to a prominent view that infants learn to extract perceptual cues from different sources about people’s emotions under different environmental and social contexts, and suggest naturalistic approaches to further advance our understanding of the development of emotion processing of body expressions.